Kepatuhan Pajak Bumi dan Bangunan: Mengkaji Kepercayaan dan Transparansi - Yanto, Alif Faruqi Febri; Rahmawati, Apriana; Firdaus, Mohammad Iqbal (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2024)
This research aims to obtain empirical evidence regarding the influence of trust and the level of transparency on the level of compliance of Land and Building Taxpayers. The implementation of this research involved land and building tax payers in Paser Regency as research subjects. The population in this study was 97.504 taxpayers with the convenience sampling method used to select 100 respondents as the research sample. Data was collected through the use of a questionnaire and then using multiple linear regression techniques. Based on the results of the analysis, it can be concluded that trust, transparency and the application of sanctions have a positive effect on the level of taxpayer compliance.Keywords: Tax compliance; Trust; Transparency